Electroacupuncture exerts prolonged analgesic and neuroprotective effects in a persistent dental pain model induced by multiple dental pulp injuries: GABAergic interneurons-astrocytes interaction - Ballon Romero, Sharmely Sharon; Fuh, Lih-Jyh; Hung, Shih-Ya; Lee, Yu-Chen; Huang, Yu-Chuen; Chien, Szu-Yu; Chen, Yi-Hung (Frontiers in Immunology, 2023)
Pain within the trigeminal system, particularly dental pain, is poorly understood. This study aimed to determine whether single or multiple dental pulp injuries induce persistent pain, its association with trigeminal central nociceptive pathways and whether electroacupuncture (EA) provides prolonged analgesic and neuroprotective effects in a persistent dental pain model. Models of single dental pulp injury (SDPI) and multiple dental pulp injuries (MDPI) were used to induce trigeminal neuropathic pain. The signs of dental pain-related behavior were assessed using the mechanical head withdrawal threshold (HWT). Immunofluorescence and western blot protocols were used to monitor astrocyte activation, changes in apoptosis-related proteins, and GABAergic interneuron plasticity. SDPI mice exhibited an initial marked decrease in HWT from days one to 14, followed by progressive recovery from days 21 to 42. From days 49 to 70, the HWT increased and returned to the control values. In contrast, MDPI mice showed a persistent decrease in HWT from days one to 70. MDPI increased glial fibrillary acidic protein (GFAP) and decreased glutamine synthetase (GS) and glutamate transporter-1 (GLT1) expression in the Vi/Vc transition zone of the brainstem on day 70, whereas no changes in astrocytic markers were observed on day 70 after SDPI. Increased expression of cleaved cysteine-aspartic protease-3 (cleaved caspase-3) and Bcl-2-associated X protein (Bax), along with decreased B-cell lymphoma/leukemia 2 (Bcl-2), were observed at day 70 after MDPI but not after SDPI. The downregulation of glutamic acid decarboxylase (GAD65) expression was observed on day 70 only after MDPI. The effects of MDPI-induced lower HWT from days one to 70 were attenuated by 12 sessions of EA treatment (days one to 21 after MDPI). Changes in astrocytic GFAP, GS, and GLT-1, along with cleaved caspase-3, Bax, Bcl-2, and GAD65 expression observed 70 days after MDPI, were reversed by EA treatment. The results suggest that persistent dental pain in mice was induced by MDPI but not by SDPI. This effect was associated with trigeminal GABAergic interneuron plasticity along with morphological and functional changes in astrocytes. EA exerts prolonged analgesic and neuroprotective effects that might be associated with the modulation of neuron-glia crosstalk mechanisms.